2016
DOI: 10.1111/joms.12203
|View full text |Cite
|
Sign up to set email alerts
|

Managing for Political Corporate Social Responsibility: New Challenges and Directions for PCSR 2.0

Abstract: This article takes stock of the discourse on 'political CSR' (PCSR), reconsiders some of its assumptions, and suggests new directions for what we call 'PCSR 2.0'. We start with a definition of PCSR, focusing on firms' contribution to public goods. We then discuss historical antecedents to the debate and outline the original economic and political context. The following section explores emerging changes in the institutional context relevant to PCSR and reconsiders some of the assumptions underlying Habermas' th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
375
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(384 citation statements)
references
References 166 publications
(191 reference statements)
4
375
0
5
Order By: Relevance
“…One predominant term that has been coined by some authors is that of 'political CSR' (Scherer and Palazzo 2011;Scherer et al 2016), to describe the role of private businesses in wider societal governance. This debate refers to the political processes resulting in authoritative allocation of values and resources in society-a role initially ascribed to governments, certainly in liberal democracies.…”
Section: Contemporary Approaches To Theorize Csrmentioning
confidence: 99%
“…One predominant term that has been coined by some authors is that of 'political CSR' (Scherer and Palazzo 2011;Scherer et al 2016), to describe the role of private businesses in wider societal governance. This debate refers to the political processes resulting in authoritative allocation of values and resources in society-a role initially ascribed to governments, certainly in liberal democracies.…”
Section: Contemporary Approaches To Theorize Csrmentioning
confidence: 99%
“…There is an underlying assumption in political CSR that a deliberative process of corporate engagement with state and civil society actors can lead to a more democratic public sphere (Scherer and Palazzo, 2016 (Bebbington et al, 2008;Gardner et al, 2012;Kraemer et al, 2013).…”
Section: The Business Of Extractionmentioning
confidence: 99%
“…In developing a theory of political CSR, Scherer and Palazzo (2011) and in a later formulation (Scherer et al, 2016) conceptualize power mainly in relation to the declining ability of states to regulate multinational corporations. Their conceptualization of politics as 'public deliberations, collective decisions and the provision of public goods' (Scherer et al, 2016: 276) without taking into account that all of these are outcomes of power relations is problematic.…”
Section: Power and Legitimacy In Csr Governancementioning
confidence: 99%
“…In this regard, some have noted that "regulatory voids have led to a political role for business" (Reinecke & Ansari, 2016, p. 300), and, in relation to peace and conflict issues, that companies are "highly political actors and have long been so" (Ford, 2015, p. 457). In a sense this relates to a broader literature on political CSR (Scherer, Rasche, Palazzo, & Spicer, 2016), but more in-depth studies have shown how companies not only struggle with these issues, especially in the most problematic (fragile) contexts, but also try to navigate through them, together with other stakeholders, to improve living conditions of communities (e.g. Kolk & Lenfant, 2013, 2015b.…”
Section: Company Contributions To Local Developmentmentioning
confidence: 99%